School – Possibility or (new) Risk for Young Females in Correctional Institutions - Ivana Jeđud Borić; Anja Mirosavljević (Center for Educational Policy Studies Journal)
In this paper, the authors deal with the education of girls in a Croatian correctional institution as a risk factor for social exclusion based on the data obtained via semi-structured interviews with experts and the girls and via the documentation analysis method. In this regard, the paper deals with two perspectives, i.e. the girls’ and experts’, in the context of risks related to schooling, intertwining these risks through the past, present and future, according to the stories of the research participants. The authors compare the perspectives given and explore the questions related to possibilities of the education of girls in correctional institutions.